Microbial Composition and Functional Diversity Differ Across Urban Green Infrastructure Types - Gill, Aman S.; Purnell, Kai; Palmer, Matthew I.; Stein, Jaime; McGuire, Krista L. (Frontiers in Microbiology, 2020)
Functional and biogeographical properties of soil microbial communities in urban ecosystems have long been neglected despite their role in metabolic processes underlying valuable ecosystem services. The worldwide emergence of engineered habitats in urban landscapes—green roofs, bioswales and other types of soil-based green infrastructure—highlights the importance of developing a predictive understanding of how environmental changes affect the community assembly processes that shape urban microbial diversity and functioning. In this study we investigated 1) whether engineered green roofs and bioswales in New York City had distinct microbial community composition and trait-associated diversity compared to non-engineered soils in parks and tree pits, and 2) if these patterns were consistent with divergent community assembly processes associated with engineered specifications of green infrastructure habitats. Using 16S- and ITS- based metagenomic amplicon sequencing, we found that green roofs and bioswales each have distinct bacterial and fungal communities. Community composition and diversity were not significantly associated with geographic distance, suggesting that the processes structuring these differences are related to aspects of the habitats themselves. Bioswales, and to a lesser extent green roofs, also contained increased functional potential based on the diversity and abundance of taxa associated with nitrogen cycling, biodegradation, decomposition and traits positively associated with plant growth. We discuss these results in the context of community assembly theory, concluding that urban soil microbial community composition and diversity in engineered habitats are driven largely by deterministic, niche-based selection, whereas stochastic processes are more important among non-engineered soils.